The Wrangling Friends or Opposition in Disorder. - [J.N.]? (Fores, S. W., 1791)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Canada Bill; French Constitution; Burke, Edmund, 1729-1797; Great Britain -- Politics and government -- 1760-1820